THE ROLE OF TRAINING IN PROMOTING OUTSTANDING PERFORMANCE - M. M. Zahraa; Yassin Alwan (Scholar Express Journals, 2023)
The current study aims to determine the role of training and its impact on the exceptional performance in the Hilla textile factory, taking into account that this industry is one of the most significant, and that the speed of developments by employing training, which helps to grow the organization's capabilities in various and different fields, which aims to enhance the exceptional performance in its affiliated industries, where The following query is the research issue (Is there a role for training in enhancing the outstanding performance of service organizations represented by the Hilla Textile Factory) The research's hypothesis, which describes the nature of the relationship between the independent variable training and the dependent variable, outstanding performance, and its dimensions, was used to formulate the correlation and influence hypotheses toorder to clarify the relationship between the research variables (job satisfaction, flexibility, productivity and the search for resources). A validity, reliability, and distribution moderation test were performed on the questionnaire once it was chosen as the primary tool for data collection and analysis.
Keywords: training; organizational effectiveness